2018
DOI: 10.1108/jfc-01-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining the effectiveness of Economic and Financial Crimes Commission (EFCC) in tackling corruptions in Nigeria

Abstract: Purpose The purpose of this paper is to appraise the Nigerian Economic and Financial Crimes Commission (EFCC) of their role in tackling systemic corruptions and to associate how institutional and organizational factors influence the performance of the EFCC. Design/methodology/approach Data were gathered through in-depth interviews, non-participatory observations and documentary analysis. Findings The results of the integrative analysis show that the EFCC has apparently been ineffective, and further improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(58 reference statements)
0
3
0
2
Order By: Relevance
“…However, other group of studies on EFC. found that among anti-bribery institutions in Nigeria the EFCC has to certain extent leave up to expectation (Umar et al , 2017; Suleiman et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, other group of studies on EFC. found that among anti-bribery institutions in Nigeria the EFCC has to certain extent leave up to expectation (Umar et al , 2017; Suleiman et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is normally carried out by forensic scientists as interpreters and examiners of facts and evidence in legal case that also gives expert opinion concerning their findings in a court of law. Fyneface and Oseiweh (2017) affirm that forensic accounting is essential investigative device for the detection of fraud Umar et al (2017) opined that forensic accounting helps in introducing effective internal control and fraud prevention in an organization. He also described forensic accounting as the mixture of auditing and investigation skills.…”
Section: Forensic Accounting Techniquesmentioning
confidence: 99%
“…The Nigerian government established the EFCC in 2002 to address multiple variations of economic crimes in order to repair Nigeria's reputation. 37,45,46,47 Cybercriminals are not the only group responsible for tarnishing the country's global image; 22,33,34,48 they share this responsibility with many public officials. 22,33,34,48 The EFCC's primary aim is to address fraudulent and corrupt practices.…”
Section: Economic and Financial Crimes Commission (Efcc)mentioning
confidence: 99%